The role of National Immunization Technical Advisory Groups in advising COVID-19 immunization policy during the pandemic: lessons from the Federation of Bosnia and Herzegovina - Musa, Sanjin; Jacques-Carroll, Lisa; Palo, Mirza (Frontiers in Public Health, 2023)
A National Immunization Technical Advisory Group (NITAG) is a multi-disciplinary body of experts that provides evidence-based recommendations on immunizations to policy-makers to assist them in making immunization policy and program decisions. NITAGs faced challenges in making evidence-based recommendations for COVID-19 vaccines during the COVID-19 pandemic due to the new vaccine products available in a short time period and limited available data on vaccine effectiveness and vaccine safety. The authors reviewed the process used by the NITAG in the Federation of Bosnia and Herzegovina, called the expert body, to develop COVID-19 vaccine recommendations. The article reviews the evidence that was considered by the expert body when developing 23 recommendations on COVID-19 vaccination and describes the challenges and successes faced by the body. The expert body recommendations led to the successful roll-out of COVID-19 vaccines and provided guidance for COVID-19 vaccination during the pandemic. The expert body plans to improve its work and procedures for developing routine immunization recommendations with the support of the WHO Regional Office for Europe.